Perinatal history of patients with encopresis - A. A. Bebenin; S. V. Grechanyi (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The aim of the study was to study the perinatal history of children suffering from inorganic encopresis, namely: the prevalence of pathology of pregnancy and childbirth in the mothers of these patients in comparison with a healthy population.Materials and Methods. The data of the perinatal anamnesis of children and adolescents aged 5 to 13 years who applied to the State Medical Institution with «SOCPB» with complaints of fecal incontinence (main group — 192 people), as well as healthy children aged 5 to 13 years, whose parents revealed a voluntary desire to participate in the study (control group — 100 people). Clinicalpsychopathological and clinical-anamnestic research methods were used in the work.Results. The results of the study showed the presence of a predominant burden of the perinatal period with pathological conditions in patients with encopresis compared with a healthy population, while 8 of the 14 factors had predictive power and entered the logistic regression equation with a high level of statistical significance (p<0.05 for all factors). The data on the statistically higher prevalence of chronic diseases of the gastrointestinal tract of mothers with children suffering from encopresis, having the greatest influence on the dependent variable and with the highest modulo value of the regression coefficient (B0=-3.117) can be regarded as a hereditary predisposition to diseases of the gastrointestinal tract, expressed in the weakness of arbitrary control of intestinal peristalsis and defecation in children. Also, for the first time, a higher incidence of the transference factor in the main group was revealed, which had never been described before in relation to encopresis.Conclusion. The results obtained during the study confirm the influence of the residual organic factor on the etiopathogenesis of encopresis in children. At the same time, for the first time, a statistical pattern was revealed clarifying the role of a number of factors of perinatal damage to the nervous system in the formation of fecal incontinence in children, which expands the possibilities of forecasting with the most effective psychoprophylaxis.